Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4162/nrp.2013.7.5.409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium intake, milk and dairy product intake, and blood vitamin D level on osteoporosis risk in Korean adults: analysis of the 2008 and 2009 Korea National Health and Nutrition Examination Survey

Abstract: This study was performed to determine the effects of dietary calcium (Ca) intake, milk and dairy product intake, and serum vitamin D level on bone mineral density. The survey data from the 2008-2009 Korea National Health and Nutrition Examination Survey (KNHANES) for adults (3,819 males, 5,625 females) aged > 20 years were examined; osteoporosis was defined according to the standards for Asian populations (T-score < -2.5). The risk for osteoporosis significantly decreased as Ca intake increased; this effect pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Significant associations were noted with hypertension and periodontal disease, 35 and periodontal disease was associated with metabolic syndrome 36 . Previous studies reported that calcium intake affected bone mineral density, peak bone mass, and calcium balance and was important in the maintenance of bone health 37,38 . Vitamin D is involved in the proper mineralization of bone, and the intake of vitamin D is necessary for the maintenance of healthy bones 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations were noted with hypertension and periodontal disease, 35 and periodontal disease was associated with metabolic syndrome 36 . Previous studies reported that calcium intake affected bone mineral density, peak bone mass, and calcium balance and was important in the maintenance of bone health 37,38 . Vitamin D is involved in the proper mineralization of bone, and the intake of vitamin D is necessary for the maintenance of healthy bones 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The Korean Natl. Health and Nutrition Examination Survey (KNHANES) results from 9444 adults found that both dietary calcium and vitamin D status impacted osteoporosis incidence in a population with typically low calcium and dairy food intake (Hong and others ). As calcium intake and serum vitamin D levels increased in this group, osteoporosis risk decreased significantly.…”
Section: Bone Healthmentioning
confidence: 99%
“…One of the most important mineral partnerships is that of calcium and phosphorus, with the calcium/phosphorus ratio in bone being 2.2:1 166 . An intake ratio of <1.0 was associated with nephrocalcinosis in rats but increasing the ratio to 1.3 inhibited calcification development 167 , while a low intake ratio increased osteoporosis risk in Koreans 168 and increased bone resorption markers 169 but a ratio of at least ≥0.74 benefited bone among younger females 87,170 . Although phosphorus restriction increases serum ionised calcium 70 , phosphorus supplementation was also associated with decreased urinary calcium excretion 126,171 , suggesting that calcium is retained to bind the phosphorus.…”
Section: Other Multinutrient Interactionsmentioning
confidence: 97%